Effect of Yb: Fiber laser on surface roughness and wettability of titanium - Dündar Yılmaz Berivan; Halil Tepe İbrahim; Nigiz Remzi; Seyfioğlu Polat Zelal; Mutluay Unal Server (Balkan Stomatological Society, 2022)
Background/Aim: In recent years, the role of computer aided design (CAD) and computer aided manufacturing (CAM) in dentistry has increasingly become important. However, the influence of different Yb: fiber laser applications on surface roughness of CAD/CAM implant has rarely been studied. The aim of this study is to investigate the effect of different Yb: fiber laser parameters on the surface roughness of CAD/CAM titanium. Material and Methods: Titanium samples, produced by CAD/CAM, were divided into 11 groups according to laser parameters such as scanning types (ST), application angles (AA) and hatch interval (HI). The surface roughness of CAD/CAM titanium was examined for each group. Wettability contact angles (CA) were also determined. Results: The highest surface roughness (43 mm) value was obtained for Group 10 (three-ways ST, 60o AA, 0.07mm HI). The lowest value (2.77 mm) after control group was obtained for Group 6. Surface roughness values, for Group 3, Group 9 and Group 10 were significantly higher than for the other groups (P= 0.000). In contact angle evaluations, the highest contact angle (144o) was observed in Group 10, while the lowest (95o) was observed in control group. Conclusions: Surface roughness was dependent on mixed effect of the laser application parameters. Three-ways ST, 60o AA, 0.07mm HI provided highest surface roughness and wettability contact angles. The surface roughness values of one-way ST, 0.06 mm HI, two-ways HT, 45o AA and 0.08 mm HI and three-ways ST, 60o AA and 0.07 mm HI were significantly higher than for the other groups (P=0.000).